Strategi Komisi Pemilihan Umum Kota Palangka Raya dalam Meningkatkan Partisipasi Pemilih GEN-Z dalam Pemilu Tahun 2024 Melalui Program “Goes To Campus, Scool And Pesantren” - Nurul Ramadani; Siti Apriyani Rosu; Irfan Dayu Pradana; Akbar Rahmat Dani; Kamal Hasuna (Nusantara Mengabdi Kepada Negeri, 2025)
Considering the importance of the involvement of the younger generation in the democratic process, the KPU launched the "Goes To Campus, School and Islamic Boarding School" program as an initiative to bring young voters closer to the election process. Through this program, the KPU carries out outreach in various educational institutions, including campuses, schools and Islamic boarding schools, with the aim of providing a better understanding of voting rights, the importance of participation, and voting mechanisms. The research method used is a qualitative approach with data collection through interviews, observation and documentation studies. The research results show that this program has succeeded in increasing GEN-Z voters' awareness and interest in participating in the election, although there are still challenges in terms of access to information and understanding of the election process. It is hoped that this article will provide insight for the KPU and other stakeholders in designing more effective strategies to involve the younger generation in democracy.